2014
DOI: 10.4236/fns.2014.518189
|View full text |Cite
|
Sign up to set email alerts
|

Petit-Suisse Cheese Production with Addition of Probiotic <i>Lactobacillus</i> <i>casei</i>

Abstract: Growing concern to increase life expectancy has promoted several studies in the field of nutrition, especially those on food and their effects on the human body. Assays have been performed to improve their nutritional quality. In fact, there is considerable interest in encouraging development of new ingredients, with the innovation in food products and the establishment of new market niches for these ingredients. The global market for functional foods is growing and always envisages new products with functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…So, the reduction in their viability is natural. Xong-Xin et al On the contrary, Barros and De Carvalho Delfino (2014) reported no meaningful difference in Lactobacillus casei viability during 30 days in petit-Suisse cheese as the pH did not pass 4.2 during this time due to buffer capacity of nutrients in milk (phosphates, citrate, peptones). They also reported that lactobacillus casei BGP 93 was resistant to acid (up to pH=3), consequently, it was not affected by acidity.…”
Section: Lactobacillus Paracasei Viability Of Probiotic Uf Cheese Samples During Cold Storagementioning
confidence: 96%
“…So, the reduction in their viability is natural. Xong-Xin et al On the contrary, Barros and De Carvalho Delfino (2014) reported no meaningful difference in Lactobacillus casei viability during 30 days in petit-Suisse cheese as the pH did not pass 4.2 during this time due to buffer capacity of nutrients in milk (phosphates, citrate, peptones). They also reported that lactobacillus casei BGP 93 was resistant to acid (up to pH=3), consequently, it was not affected by acidity.…”
Section: Lactobacillus Paracasei Viability Of Probiotic Uf Cheese Samples During Cold Storagementioning
confidence: 96%